Culicoides allergens expressed in insect cells induce sulphidoleukotriene release from peripheral blood leukocytes of horses affected with insect bite hypersensitivity - Jonsdottir, Sigridur; Stefansdottir, Sara Björk; Mirkovitch, Jelena; Ziegler, Anja; Torsteinsdottir, Sigurbjörg; Marti, Eliane (Frontiers in Immunology, 2025)
IntroductionInsect bite hypersensitivity (IBH) is an IgE-mediated dermatitis in horses caused by bites of Culicoides spp. The allergens are salivary gland proteins from these insects, and nine major allergens from Culicoides obsoletus have been identified and expressed in E. coli. However, proteins expressed in procaryotic systems have limitations in cellular assays, particularly in functional assays assessing the allergen-induced release of mediators in vitro, such as sulphidoleukotrienes (sLT) from basophils. The aims of the study were to produce functional Culicoides allergens in insect cells, to assess their allergenicity using a sLT release assay, and to relate the sLT release with IgE sensitization to the respective allergens using ELISA.MethodsEight major Culicoides obsoletus allergens (Cul o 1P, Cul o 2P, Cul o 3, Cul o 5, Cul o 7, Cul o 8, Cul o 9, and Cul o 11) were expressed in insect cells and purified. sLT release from peripheral blood leukocytes (PBL) following stimulation with the eight Culicoides allergens was measured in 28 IBH-affected and 24 healthy control horses. Allergen-specific serum IgE levels was determined by ELISA.ResultsThe eight major allergens were successfully expressed in insect cells and purified. All allergens induced a significantly higher sLT release from PBL of IBH-affected horses compared to healthy controls. There was a high correlation and substantial to excellent agreement between sLT release and serum IgE levels for six Culicoides allergens, while for two, the agreement was moderate. Positivity rates in IBH horses were usually higher in IgE serology, but more false-positive results were obtained. The allergens performing best in both assays were Cul o 3, Cul o 8, and Cul o 9, with very high specificity and good sensitivity.DiscussionInsect-cell-expressed Culicoides recombinant allergens are functionally relevant and will open new opportunities for the study of Culicoides hypersensitivity not only in horses but also potentially in human patients or other species. They will also greatly improve IBH diagnostics using cellular assays and IgE serology.